Laozi’s Influence on Contemporary Rap Music: A Study of Cultural Protection and Inheritance - Ma, Simeng; Ts, Madya; Ismail, Adzrool ldzwan bin (Journal of Ecohumanism, 2024)
This study investigates the influence of Laozi’s teachings on contemporary rap music, focusing on themes of cultural protection and inheritance. Through a mixed-methods approach, qualitative and quantitative analyses were conducted to explore the extent of Laozi's influence in rap lyrics. Qualitative analysis involved in-depth examination of lyrical content to identify thematic parallels with Laozi's philosophy, while quantitative analysis quantified instances of Laozi references in selected rap songs. The results reveal a steady increase in Laozi references in rap music over time, with prevalent themes including harmony, self-awareness, and balance. Geographic distribution highlights a global reach of Laozi-inspired rap, transcending cultural boundaries. Collaboration patterns, sentiment analysis, and commercial performance further elucidate the multifaceted relationship between Laozi's teachings and contemporary rap culture. This study contributes to understanding the dynamics of cultural transmission and adaptation in the modern music industry, showcasing the enduring relevance of ancient wisdom in shaping artistic expression.